2018
DOI: 10.4142/jvs.2018.19.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Association between endotoxin levels in dust from indoor swine housing environments and the immune responses of pigs

Abstract: Indoor animal husbandry environments are inevitably contaminated with endotoxins. Endotoxin exposure is associated with various inflammatory illnesses in animals. This cross-sectional study evaluated the relationship between the degree of endotoxin exposure and the cellular and humoral immune profiles of fattening pigs. Blood samples were taken from the jugular vein of 47 pigs from ten pig farms in Korea. Whole blood cell counts and plasma immunoglobulin (Ig) classes were determined. Peripheral-blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…MRSA alone (CG), the increase of the total leukocytes due to a significant increase of neutrophils detected in the EG is interpreted as being induced by endotoxin. Alterations in the peripheral blood of endotoxin-exposed pigs were also found by other groups [10,29]. Thereby, our data imply that the effect of airborne endotoxin in our aerosol chamber on the immune system is comparable to those in animals continuously exposed to high levels of endotoxin in pig barns.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…MRSA alone (CG), the increase of the total leukocytes due to a significant increase of neutrophils detected in the EG is interpreted as being induced by endotoxin. Alterations in the peripheral blood of endotoxin-exposed pigs were also found by other groups [10,29]. Thereby, our data imply that the effect of airborne endotoxin in our aerosol chamber on the immune system is comparable to those in animals continuously exposed to high levels of endotoxin in pig barns.…”
supporting
confidence: 86%
“…Furthermore, in a field study, discrepancies were found in the immune response between pigs and broilers despite the equal endotoxin concentration in the environment of investigated barns [29]. Roque et al explained their findings with the longer endotoxin exposure of pigs (5-month fattening period) compared to broilers (1-month fattening period) [29]. The authors concluded that endotoxin weakens the piglets' immune defense against pathogens underlining that a possible role of airborne endotoxin favoring MRSA colonization in field cannot be neglected.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In comparison with pigs raised in barns with low-bacterial endotoxin levels, there was an increase of white blood cells in pigs exposed to high-endotoxin levels. In addition, peripheral blood mononuclear cells (PBMC) collected from high-exposure pigs had greater plasma immunoglobulin (Ig) G and IgE levels but lower IgA levels than that produced by PBMCs from low-exposure pigs ( 66 ). The inflammatory capabilities of SFD have also been demonstrated in various in vitro experiments using human bronchial epithelial cells and pulmonary carcinoma cell lines ( 19 , 72 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, endotoxins found in the dust collected from CAFOs act as the primary factor in the onset of asthma and other respiratory conditions (61)(62)(63). A considerable amount of research has shown that exposure to endotoxins is especially prevalent in swine farm workers (64)(65)(66). Raising swine is a lucrative agricultural enterprise for US farmers with sales generating 26.3 billion dollars in 2017 (67).…”
Section: Introductionmentioning
confidence: 99%